We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
39
1
avatar+93 

Let \(r\) be the positive real solution to \(x^3 + \frac{2}{5} x - 1 = 0. \) Find the exact numerical value of \(r^2 + 2r^5 + 3r^8 + 4r^{11} + \dotsb.\)
 

 Jun 8, 2019
 #1
avatar
0

Solve for x:
x^3 + (2 x)/5 - 1 = 0

Bring x^3 + (2 x)/5 - 1 together using the common denominator 5:
1/5 (5 x^3 + 2 x - 5) = 0

Multiply both sides by 5:


5 x^3 + 2 x - 5 = 0

Divide both sides by 5:
x^3 + (2 x)/5 - 1 = 0

Change coordinates by substituting x = y + λ/y, where λ is a constant value that will be determined later:


-1 + 2/5 (y + λ/y) + (y + λ/y)^3 = 0

Multiply both sides by y^3 and collect in terms of y:
y^6 + y^4 (3 λ + 2/5) - y^3 + y^2 (3 λ^2 + (2 λ)/5) + λ^3 = 0

Substitute λ = -2/15 and then z = y^3, yielding a quadratic equation in the variable z:


z^2 - z - 8/3375 = 0
Find the positive solution to the quadratic equation:
z = 1/450 (225 + sqrt(51105))

Substitute back for z = y^3:


y^3 = 1/450 (225 + sqrt(51105))

Taking cube roots gives (225 + sqrt(51105))^(1/3)/(2^(1/3) 15^(2/3)) times the third roots of unity:
y = (225 + sqrt(51105))^(1/3)/(2^(1/3) 15^(2/3)) or y = -(-225 - sqrt(51105))^(1/3)/(2^(1/3) 15^(2/3)) or y = ((-1)^(2/3) (225 + sqrt(51105))^(1/3))/(2^(1/3) 15^(2/3))

Substitute each value of y into x = y - 2/(15 y):


x = ((sqrt(51105) + 225)/2)^(1/3)/15^(2/3) - 2 (2/(15 (sqrt(51105) + 225)))^(1/3) or x = -((-sqrt(51105) - 225)/2)^(1/3)/15^(2/3) - 2 (-1)^(2/3) (2/(15 (sqrt(51105) + 225)))^(1/3) or x = 2 ((-2)/(15 (sqrt(51105) + 225)))^(1/3) + ((-1)^(2/3) ((sqrt(51105) + 225)/2)^(1/3))/15^(2/3)


Bring each solution to a common denominator and simplify:
x≈0.867559241390112
x≈-0.433779620695056 - 0.982086695761143 i
x≈-0.433779620695056 + 0.982086695761143 i
Use the Real Value to sum up the sequence:


sumfor(r, 1, 10000,  (r*0.867559^(3*r-1))) = 6 1/4 

 Jun 8, 2019
edited by Guest  Jun 8, 2019

9 Online Users

avatar
avatar